ENHANCING UNIVERSITY STUDENTS' PROFESSIONAL COMPETENCE THROUGH KINESTHETIC INTELLIGENCE DEVELOPMENT (Spectrum Journal of Innovation, Reforms and Development, 2025)
This paper investigates the role of kinesthetic intelligence in enhancing the professional competence of university students in the context of modern, practice-oriented education. Kinesthetic intelligence—defined as the ability to use one’s body to express ideas, solve problems, and learn through movement—is increasingly acknowledged as a key contributor to effective vocational training and skill acquisition. Drawing from empirical evidence and recent developments in educational neuroscience, the paper outlines methods for embedding kinesthetic practices into core university curricula across various specializations. The study emphasizes the need for institutional support, inclusive instructional design, and cross-disciplinary integration to fully harness the benefits of kinesthetic intelligence. The ultimate goal is to cultivate graduates who are not only cognitively prepared but physically adept and profession-ready in dynamic labor markets.